STRATEGI MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYYAH MELALUI METODE MENGHAFAL DI TK DHARMA WANITA TAMBAKBOYO I MANTINGAN - Yudhiarti, Ndaru Putri (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2022)
Strategies to improve the ability to read hijaiyyah letters are started or introduced from an early age. The ability to read Hijaiyyah letters is about the philosophical and religious foundations of early childhood basic education, basically it must be based on philosophical and religious values held by the environment and language around the child and the religion he adheres to. This study aims to determine how to increase the ability to read hijaiyyah letters through the memorization method. This study uses a method. This research uses descriptive qualitative research methods with research subjects are students, principals, and teachers of TK Dharma Wanita Tambakboyo I. Research data obtained through interviews, observation, and documentation. The results showed that the memorization method in TK Dharma Wanita Tambakboyo I with habituation, spontaneous activities, advice, routine activities could improve students' ability to read hijaiyyah letters